The Influence of Decentralization Policy and Family Hope Program on Social Welfare in Urban Areas Through Social Assistance - Tampubolon, Khairuddin; Elazhari, Elazhari; Undang, Gunawan; Pin, Pin (UIN Sunan Gunung Djati, 2024)
The decentralization policy gives authority to local governments to design and implement programs that are in accordance with local needs, including the Family Hope Program (PKH) as one of the social protection instruments. PKH aims to improve social welfare through conditional social assistance that encourages poor people's access to education and health. This study contributes by revealing how decentralization affects the effectiveness of PKH implementation in urban areas, especially through the distribution of social assistance, and its impact on improving social welfare in Medan City. This analysis is expected to strengthen evidence-based policies in realizing equal social welfare in urban areas, especially Medan City. However, the effectiveness of this policy still requires further study to understand its specific impact on the community in Medan City. The purpose of this study was to determine the effect of the Decentralization Policy and the Family Hope Program (PKH) on Social Welfare in Medan City with the Intervening Media of the Social Assistance Program. The sample used a purposive sampling technique to obtain respondents who were relevant to the study. The research method used was quantitative research, namely by distributing questionnaires to 100 respondents from the Medan City community, North Sumatra who received Social Assistance and the Family Hope Program (PKH). The results of this study: 1) There is an influence of Decentralization Policy on Social Welfare in Medan City, North Sumatra with a value of 24.1%; 2) There is an influence of the Family Hope Program (PKH) on Social Welfare in Medan City, North Sumatra 45.7%; 3) The magnitude of the influence of the Social Assistance Program on Social Welfare partially is 2.5%; 4) The magnitude of the influence of the Decentralization Policy and the Family Hope Program (PKH) on Social Welfare in Medan City with the Intervening Media of the Social Assistance Program is: 67.5% + 2.5% = 70%.